Alopecia Areata and Scarring Alopecia Presenting During Golimumab Therapy for Ankylosing Spondylitis - Helm, Melissa M.; Haddad, MD, Stefanos (North American Journal of Medicine and Science, 2018)
Golimumab is a human monoclonal antibody useful in the treatment of a wide variety of inflammatory conditions including ankylosing spondylitis, rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis. Golimumab’s clinical efficacy is attributed to its inhibition of tumor necrosis factor alpha (TNF-α). As more individuals have been treated with anti-TNF-α therapy, increased numbers of side effects have been identified. We report a patient with a long history of ankylosing spondylitis and atopic dermatitis who noted exacerbation of his alopecia areata early on, and subsequently developed scarring alopecia and facial rash. Clinicians should be aware of the autoimmune reactions associated with golimumab to better inform decisions about therapy and management of underlying rheumatologic disease. [N A J Med Sci. 2018;11(1):22-24. DOI: 10.7156/najms.2018.110122]